Hydrodynamic modelling of tidal-fluvial flows in a large river estuary. (15th November 2018) - Sandbach, S.D.; Nicholas, A.P.; Ashworth, P.J.; Best, J.L.; Keevil, C.E.; Parsons, D.R.; Prokocki, E.W.; Simpson, C.J.
Abstract: The transition between riverine and estuarine environments is characterised by a change from unidirectional to bidirectional flows, in a region referred to herein as the Tidally-Influenced Fluvial Zone (TIFZ). In order to improve our understanding of the hydrodynamics and morphodynamics of this zone, we present a combined field and numerical modelling study of the Columbia River Estuary (CRE), USA, tidally-influenced fluvial zone. The CRE is large measuring 40 km in length and between 5 and 10 km wide. A shallow water model (Delft3D) was applied in both 2D and 3D configurations and model sensitivity to the key process parameterizations was investigated. Our results indicate that a 2D model constrained within the estuary can sufficiently reproduce depth-averaged flow within the TIFZ of a stratified estuary. Model results highlight the interactions between tidal-, fluvial- and topographic-forcing that result in depth dependent tidal rectification, and thus zones of residual sediment transport that: i) may be flood-directed along shallow channel margins and in the lee of bars, and simultaneously ii) is ebb-directed within deeper channel thalwegs. This condition is enhanced at lower discharges, but increased fluvial discharge reduces the number and size of regions with net flood-directed sediment transport and flow. These sediment transport patterns provide a mechanism to extend the bar/island topography downstream, and generate flood-directed, ebb-directed, and symmetrical bedforms, all within the same channel. Analysis of the model data reveals flood-directed sediment transport is due to both tidal variability and mean flow. These results highlight the need to include the mean flow component (M0 ) when considering the long-term morphodynamic evolution in a TIFZ. Graphical abstract: Image 1